Queering Gothic in the Romantic Age - Fincher, M. author. aut Link
VI, 205 p.
Keywords: This book argues that Gothic writing of the Romantic period is queer. Using a variety of texts, it argues that contemporary queer theory can help us to read the obliqueness and invisibility of same-sex desire in a culture of vigilance. Fincher shows how the Gothic's ambivalent gender politics destabilize heteronormative narratives.